2013
DOI: 10.1088/1612-2011/10/7/075606
|View full text |Cite
|
Sign up to set email alerts
|

ATP-induced lipid membrane reordering in the myelinated nerve fiber identified using Raman spectroscopy

Abstract: We demonstrate a successful application of Raman spectroscopy to the problem of lipid ordering with microscopic resolution in different regions of the myelinated nerve fiber. Simultaneous collection of Raman spectra of lipids and carotenoids has enabled us to characterize membrane fluidity and the degree of lipid ordering based on intensity ratios for the 1527/1160 and 2940/2885 cm −1 bands. We show that the intensity profiles of the major Raman bands vary significantly between the three major regions of myeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…More prolonged incubation time can result in the start of nerve fiber degeneration. On the other hand it was shown previously that shorter incubation times (order of few minutes) were shown not to induce any changes in the internodal region of myelin [ 7 ]. Taking into account that a myelinated nerve fiber consists approximately only of internodal regions with very small contribution of Nodes of Ranvier and paranodal regions, the processes attributed to the overall myelin reorganisation should be detectable along the whole fiber length.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…More prolonged incubation time can result in the start of nerve fiber degeneration. On the other hand it was shown previously that shorter incubation times (order of few minutes) were shown not to induce any changes in the internodal region of myelin [ 7 ]. Taking into account that a myelinated nerve fiber consists approximately only of internodal regions with very small contribution of Nodes of Ranvier and paranodal regions, the processes attributed to the overall myelin reorganisation should be detectable along the whole fiber length.…”
Section: Resultsmentioning
confidence: 93%
“…This work is a concrete example of how ATP-activated pathway can evoke a reorganisation of peripheral myelin, however the exact mechanism is unclear. Another example of a possible role of ATP in myelin restructuring comes from the previous studies of authors where an administration of extracellular ATP led to the structural changes in myelin lipids [ 7 ]. The underlying rationale of the present work is to provide an evidence that ATP can not only affect conformational and ordering properties of myelin lipids, but also change its chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…Long time has passed since the first Raman spectra from the myelin sheath of sciatic nerve were recorded [ 11 15 ]. Further investigation revealed that myelin of nerve fibers contains carotenoid molecules on its membrane which have predominantly radial-like orientation [ 9 , 10 , 12 ]. Probably, if the carotenoid molecule changes their conformation due to the changes in membrane potential, further it may create tensions in the conformation surrounding lipids of the nerve fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Probably, if the carotenoid molecule changes their conformation due to the changes in membrane potential, further it may create tensions in the conformation surrounding lipids of the nerve fiber. Thus, carotenoids can be mediators of voltage adjustment of myelin and are able to regulate interactions of ligands with lipid bilayer [ 12 ]. After that, different variations of RS were developed and applied to assess the molecular structure of myelin upon different pathologies [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, carotenoids can possibly mediate the potential-induced myelin reorganization, as well as regulate interaction of external signaling molecules with the membrane. Kutuzov et al (9) have previously employed Raman spectroscopy and showed that both lipid and carotenoid molecules are sensitive to the extracellular ATP, and thus are possible mediators of the membrane restructuring.…”
Section: Introductionmentioning
confidence: 99%